Catalyzing Innovation in Social Work Practice. (March 2017) - Traube, Dorian E.; Begun, Stephanie; Okpych, Nathanael; Choy-Brown, Mimi
Social innovation is defined by novelty and improvement. This definition requires social work practice to be more effective or efficient than preexisting alternatives. Practice innovation is accomplished by leveraging technical, social, and economic factors to generate novel interventions, diffusion or adoption of the interventions into broader use, and identification of the value created by the new approaches or processes. Innovation in social work practice is fundamentally hindered by the foundational trifecta on which the profession is built: (a) the structure of social work education, (b) diffusely focused professional organizations, and (c) siloed professional environments. This article explores the elements of social work education, professional organizations, and practice environments that impede innovation and offers recommendations for changes in each sector that can facilitate innovation.